Gravity without apologies: the science of elasticities, distance, and trade - Carrere, C; Mrázová, M; Neary, J (Oxford University Press, 2020)
Gravity as both fact and theory is one of the great success stories of recent research on international trade, and has featured prominently in the policy debate over Brexit. We first review the facts, noting the overwhelming evidence that trade tends to fall with distance. We then introduce some expository tools for understanding CES theories of gravity as a simple general-equilibrium system. Next, we point out some anomalies with the theory: mounting evidence against constant trade elasticities, and implausible predictions for bilateral trade balances. Finally, we sketch an approach based on subconvex gravity as a promising direction to resolving them.